2010
DOI: 10.1111/j.1365-2958.2010.07313.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of lipid homeostasis in mycobacteria

Abstract: SummaryMycolic acids are major components of the cell envelope of mycobacteria, such as Mycobacterium tuberculosis, and play an important role in its architecture, impermeability and interaction with the environment. Synthesis of mycolic acids is carried out by two types of fatty acid synthases (FAS) working in concert: type I FAS, a multifunctional enzyme capable of de novo synthesis of medium-chain fatty acids, and type II FAS, responsible for their elongation. In this article we report the identification an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
63
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 55 publications
0
63
1
Order By: Relevance
“…Our studies on the ⌬accD6 Mtb -P acc -accD6 Mtb mutant treated with INH suggest that P acc is regulated independently from P fasII , since P acc is insensitive to INH treatment. The findings of Salzman et al (61) support this hypothesis, showing that a palindromic motif recognized by MabR is localized uniquely in P fasII , thus suggesting that this transcriptional repressor is very unlikely to influence accD6 Mtb expression driven from the P acc promoter. However, this does not exclude the possibility that AccD6 activity is regulated following posttranslational modifications.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our studies on the ⌬accD6 Mtb -P acc -accD6 Mtb mutant treated with INH suggest that P acc is regulated independently from P fasII , since P acc is insensitive to INH treatment. The findings of Salzman et al (61) support this hypothesis, showing that a palindromic motif recognized by MabR is localized uniquely in P fasII , thus suggesting that this transcriptional repressor is very unlikely to influence accD6 Mtb expression driven from the P acc promoter. However, this does not exclude the possibility that AccD6 activity is regulated following posttranslational modifications.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, Salzman et al (61) identified a transcriptional factor (MabR) regulating FAS-II operon expression through its action on the P fasII promoter. Also, typical inhibitors of mycolic acid biosynthesis, such as isoniazid (INH), are able to induce a transcriptional response by genes placed under the control of P fasII (5,26,71,81).…”
Section: Discussionmentioning
confidence: 99%
“…The lipid transcriptional regulator FadR, a GntR family regulator, was first identified in E. coli (18,29). Other lipid transcriptional regulators recently reported include FasR of Streptomyces coelicolor (an activator of fatty acid biosynthesis) and MabR of M. tuberculosis (a repressor of genes in the cell wall mycolic acid biosynthesis pathway) (2,48). In both these bacteria, fatty acids produced in excess of the membrane phospholipid requirement may be diverted to storage granules (3,46,60).…”
Section: Discussionmentioning
confidence: 99%
“…A few transcription regulators that directly regulate the biosynthesis genes have been identified. FasR regulates the expression of the fas gene (15), while MabR (16) and FadR (17) regulate the expression of the fabD-accD6 cluster, the fasII operon (Fig. 1B).…”
mentioning
confidence: 99%